2008
DOI: 10.1093/annonc/mdn005
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the magnitude of trastuzumab effects within patient subgroups in the HERA trial

Abstract: Adjuvant trastuzumab therapy reduces the risk of relapse similarly across subgroups defined by nodal status and steroid hormone receptor status, even those at relatively low risk for relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(91 citation statements)
references
References 8 publications
6
84
0
1
Order By: Relevance
“…Our results are in keeping with those from the HERA trial, which suggested that patients with the best prognosis tumours (node negative and size 1 -2 cm) had benefit from herceptin, similar to the overall cohort (Untch et al, 2008). The 29% of patients in the BCIRG 006 trial who were node negative (Slamon et al, 2006) also derived benefits similar to those derived by the whole cohort using trastuzamab, although they were included only if they had another high-risk feature (grade, ER negative over 2 cm).…”
Section: Discussionsupporting
confidence: 89%
“…Our results are in keeping with those from the HERA trial, which suggested that patients with the best prognosis tumours (node negative and size 1 -2 cm) had benefit from herceptin, similar to the overall cohort (Untch et al, 2008). The 29% of patients in the BCIRG 006 trial who were node negative (Slamon et al, 2006) also derived benefits similar to those derived by the whole cohort using trastuzamab, although they were included only if they had another high-risk feature (grade, ER negative over 2 cm).…”
Section: Discussionsupporting
confidence: 89%
“…Prior to the advent of anti-HER2 agents such as trastuzumab, patients with HER2C disease had a poorer 5-year overall survival (Nguyen et al 2008, Park et al 2012. Interestingly, although the recent HERA trial points to a similar trastuzumab response irrespective of hormone receptor status (Untch et al 2008), there is evidence that noeadjuvant trastuzumab may be less effective in ERC/ HER2C vs ERK/HER2C tumours (Bhargava et al 2011), suggesting that the presence of the ER in HER2C tumours may be an important consideration. Conversely, the presence of HER2 in ERC tumours may also be a limiting factor for endocrine therapy, particularly since ERC/ HER2C tumours are likely to be treated with both endocrine and trastuzumab treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses from several of the randomized trials have shown a consistent benefit with trastuzumab irrespective of tumor size or nodal status. 154,287,288 The panel recommends AC followed by paclitaxel with trastuzumab, commencing with the first dose of paclitaxel, for 1 year as a preferred HER2-targeting adjuvant regimen. The TCH regimen is also a preferred regimen, especially in those with risk factors for cardiac toxicity, given the results of the BCIRG 006 study that showed superior disease-free survival in patients receiving either TCH or AC followed by docetaxel plus trastuzumab both compared with AC followed by docetaxel alone.…”
mentioning
confidence: 99%